2020
DOI: 10.1126/scitranslmed.abc5332
|View full text |Cite
|
Sign up to set email alerts
|

3C-like protease inhibitors block coronavirus replication in vitro and improve survival in MERS-CoV–infected mice

Abstract: Pathogenic coronaviruses are a major threat to global public health, as exemplified by Severe Acute Respiratory Syndrome coronavirus (SARS-CoV), Middle East respiratory syndrome coronavirus (MERS-CoV) and the newly emerged SARS-CoV-2, the causative agent of coronavirus disease 2019 (COVID-19). We describe herein the structure-guided optimization of a series of inhibitors of the coronavirus 3C-like protease (3CLpro), an enzyme essential for viral replication. The optimized compounds were effective against sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
295
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 221 publications
(301 citation statements)
references
References 56 publications
1
295
0
5
Order By: Relevance
“…They showed good performance in in vitro anti-SARS-CoV-2 study and could rapidly enter further clinical trials. Other agents were ab initio designed drugs based on 3 dimensional structure of M pro (Dai et al, 2020;Rathnayake et al, 2020;Zhang et al, 2020b), and these compounds demonstrated the advantage of more potent inhibition and specificity toward M pro .…”
Section: Resultsmentioning
confidence: 99%
“…They showed good performance in in vitro anti-SARS-CoV-2 study and could rapidly enter further clinical trials. Other agents were ab initio designed drugs based on 3 dimensional structure of M pro (Dai et al, 2020;Rathnayake et al, 2020;Zhang et al, 2020b), and these compounds demonstrated the advantage of more potent inhibition and specificity toward M pro .…”
Section: Resultsmentioning
confidence: 99%
“…2b and 2d). Previous structure-activity relationship studies of GC376 indicate that P4 substitution is important, while P3 substitution does not contribute significantly to the binding affinity, as it is solvent exposed 3,8,9,15 . Similarly, the overlaying structures of SARS-CoV M pro + ML188 (R) (PDB: 3V3M) and SARS-CoV-2 M pro + UAWJ247 (PDB: 6XBH) suggested that the 4-tert-butyl at the P2 substitution of ML188 (R) can be replaced by phenyl to occupy the extra space in the S2 pocket ( Figs.…”
Section: Rational Design Of Non-covalent Sars-cov-2 M Pro Inhibitorsmentioning
confidence: 96%
“…Given that SARS-CoV-2 does not encode any neuraminidase protein, neuraminidase inhibitors such as oseltamivir, zanamivir or lamivir are not thought to be effective for treating patients with COVID-19 . However, some studies have found that drugs including arbidol (Zhu et al, 2020), fusion peptide (EK1) (Xia et al, 2019), ganciclovir (Lai et al, 2020), Abelson (Abl) kinase inhibitor (imatinib) (Bernal-Bello et al, 2020), metronidazole (Gharebaghi et al, 2020), antiprotozoal drugs (nitazoxanide and ivermectin) (Mahmoud et al, 2020;Peña-Silva et al, 2020), and 3CL(Pro) inhibitors (Rathnayake et al, 2020) are efficacious when used to prevent SARS-CoV-2 infections in vitro. However, their safety and efficacy in preventing COVID-19 in humans remains to be determined.…”
Section: Other Drugsmentioning
confidence: 99%